DIRECT INHIBITION OF PHYTOPHTHORA INFESTANS, THE CAUSAL ORGANISM OF LATE BLIGHT OF POTATO BY BACILLUS ANTAGONISTS - Ajay, S.; Sunaina, V. (Potato Journal, 2013)
Bacterial antagonism was investigated as the possible method for control of late blight of potato caused by Phytophthora infestans. The antagonist Bacillus subtilis B5, when tested by dual culture technique, was found the most active agent in inhibiting growth of P. infestans. The antagonist B5 recorded 67.21% reduction in pathogen growth after 2 days of incubation, 86.57% after 4 days of incubation, 89.52% after 6 days of incubation and 91.15% after 8 days of incubation.